Ultrasound Imaging of the Sciatic Nerve - Cocco, Giulio; Ricci, Vincenzo; Corvino, Antonio; Pacini, Patrizia; Boccatonda, Andrea; Naňka, Ondřej; Sensi, Stefano L.; Caulo, Massimo; Delli Pizzi, Andrea (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
The sciatic nerve (SN) is the biggest nerve in the human body and innervates a large skin surface of the lower limb and several muscles of the thigh, leg, and foot. It originates from the ventral rami of spinal nerves L4 through S3 and contains fibers from both the posterior and anterior divisions of the lumbosacral plexus. After leaving the neural foramina, the nerve roots merge with each other forming a single peripheral nerve that travels within the pelvis and thigh. Non-discogenic pathologies of the SN are largely underdiagnosed entities due to nonspecific clinical tests and poorly described imaging findings. Likewise, to the best of our knowledge, a step-by-step ultrasound protocol to assess the SN is lacking in the pertinent literature. In this sense, the aim of the present manuscript is to describe the normal sono-anatomy of the SN from the greater sciatic foramen to the proximal thigh proposing a standardized and simple sonographic protocol. Then, based on the clinical experience of the authors, a few tips and tricks have been reported to avoid misinterpretation of confounding sonographic findings. Last but not least, we report some common pathological conditions encountered in daily practice with the main purpose of making physicians more confident regarding the sonographic “navigation” of a complex anatomical site and optimizing the diagnosis and management of non-discogenic neuropathies of the SN.
Keywords: METHODS & TECHNIQUES; ultrasound; sciatic nerve; dynamic ultrasound; THEMES; anatomy; non-discogenic pain